Implementation of barokah farm business process modeling in kampar regency in accelerating digital transformation using business process model and nation (BPMN) - Firmananda, Fahmi Iqbal; Jati, Putri Zulia; Syafriani, Mona; Aryadi, Aryadi (International Journal of Applied Finance and Business Studies, 2025)
Digital transformation is an important need for MSMEs in the livestock sector to increase efficiency and competitiveness. Barokah Farm, as an egg-laying chicken farming business in Kampar Regency, faces various business process challenges, most of which are still carried out manually. This study aims to map the Barokah Farm business process using the Business Process Model and Notation (BPMN), identify digitalization opportunities, and provide recommendations for process improvements. This study contributes to the scarce BPMN literature in agribusiness by being one of the first to model small-scale poultry farming processes in Indonesia, offering both theoretical insights on BPMN’s adaptability to resource-constrained UMKM and practical guidance for improving efficiency, reducing costs, and supporting digital transformation initiatives. The method used is a case study with a qualitative and quantitative descriptive approach, through interviews, field observations for six months, and process simulations using the Bizagi Modeler application. The results of the study show that digitalization of the ordering process, procurement of raw materials, and product delivery can increase operational efficiency. The implementation of the recommended digital solution is estimated to reduce the total process duration by 38.89%. The highest efficiency occurs in the ordering process with a reduction in time of up to 66.67%, followed by product delivery within the city (44.44%), product procurement (40%), and product delivery outside the city (31.58%). The systematic application of BPMN not only helps in visualizing more effective business processes but also supports the acceleration of digital transformation at Barokah Farm.